Phenomenology of Islamic Education Management amid Complexity and Ambiguity in the Digital Disruption Era - Eva Nuraeni; Irawan Irawan; Rohmat Mulyana Sapdi (JURNAL ISLAM NUSANTARA, 2025)
This study explores how Islamic education managers experience and manage complexity and ambiguity in the era of digital disruption through reflective, value-based practices. Digital transformation has intensified tensions between technological adaptation and the preservation of Islamic ethical and spiritual foundations within educational governance. These tensions often manifest as policy uncertainty, generational gaps, and challenges in aligning technology with institutional identity. This research adopts a qualitative phenomenological design and is conducted in selected Islamic boarding schools, using in-depth interviews, observations, and document analysis. Data were analysed through iterative processes of data condensation, thematic display, and verification to capture the essence of managerial lived experiences. The findings reveal that value-based management grounded in tauhid, amanah, justice, and maslahah provides a stable framework for navigating uncertainty. Curriculum integration and human resource management emerge as ongoing epistemological and axiological negotiations rather than fixed administrative procedures. Musyawarah and philosophical reflection function as central adaptive mechanisms, enabling collective sense-making, ethical deliberation, and contextual responses to digital challenges. Technology is positioned as a supportive means for education and da‘wah, not as a determinant of institutional direction. This study contributes by reconceptualising Islamic education management as an interpretive and ethical practice and recommends strengthening reflective leadership and dialogical governance to sustain adaptive capacity.